MUTASI, ROTASI, DEMOSI DAN PROMOSI - Mhd Manshur; Afriza (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2024)
In this article, we discuss how to evaluate and reward teaching staff through transfers, rotations, demotions and promotions. Educators need to pay great attention to developing and improving teacher qualifications, if we want to improve the quality of education. Organizations use rotations, transfers, demotions and promotions to meet internal change needs, increase human resources and optimize workforce placement in the hope that teaching staff will develop further. This article also discusses the aims and benefits of implementing transfers, rotations, demotions and promotions in an effort to improve the quality of teaching staff. Thus, the implementation of transfers, rotations, demotions and rotations is very important to achieve national education goals and the progress of educational institutions